Diffusion measurements in a 3DoF Hamiltonian flow - Mestre, Martín Federico (2011)
We present measurements of diffusion phenomenae in the phase space of a three degree of freedom guasz-integrable Hamiltonian flow. By tracking the evolution of the variance of ensembles of test particles, we characterize the diffusion as basically anomalous. We find a time range in which it can be considered as a subdiffusion process and other in which it can be considered as a normal diffusion process. In the former case we fit Hurst exponents and in the latter case we compute diffusion coefficients based on the rate of growth of the variances.